A boil-off gas utilization for improved performance of heavy duty gas turbines in combined cycle - Mazzoni, Stefano (2021)
The storage of the natural gas under liquid phase is widely adopted and one of the intrinsic phenomena occurring in liquefied natural gas is the so-called boil-off gas; this consists of the regasification of the natural gas due to the ambient temperature and loss of adiabacity in the storage tank. As the boil-off occurs, the so-called cold energy is released to the surrounding environment; such a cold energy could potentially be recovered for several end-uses such as cooling power generation, air separation, air conditioning, dry-ice manufacturing and conditioning of inlet air at the compressor of gas turbine engines. This paper deals with the benefit corresponding to the cooling down of the inlet air temperature to the compressor, by means of internal heat transfer recovery from the liquefied natural gas boil-off gas cold energy availability. The lower the compressor inlet temperature, the higher the gas turbine performance (power and efficiency); the exploitation of the liquefied natural gas boil-off gas cold energy also corresponds to a higher amount of air flow rate entering the cycle which plays in favour of the bottoming heat recovery steam generator and the related steam cycle. Benefit of this solution, in terms of yearly work and gain increase have been established by means of ad hoc developed component models representing heat transfer device (air/boil-off gas) and heavy duty 300 MW gas turbine. For a given ambient temperature variability over a year, the results of the analysis have proven that the increase of electricity production and efficiency due to the boil-off gas cold energy recovery has finally yield a revenue increase of 600,000€/year.